Analisis Pengaruh Intellectual Capital terhadap Financial Performance Perusahaan Energi di Indonesia - Putri, Shieny Tan; Hesniati, Hesniati (Jurnal Maksipreneur, 2024)
This study was conducted to determine the effect of intellectual capital on the financial performance of Indonesian companies engaged in the energy sector. This study is a causal-comparative study with company performance as the dependent variable, and intellectual capital efficiency (ICE) as the independent variable consisting of human capital efficiency (HCE), structural capital efficiency (SCE), relational capital efficiency (RCE), and capital employed efficiency (CEE). This study also uses two control variables, i.e. leverage and size. The sample studied was 21 Indonesian companies listed in the energy sector on the Indonesia Stock Exchange (IDX) which were obtained through the purposive sampling method. This study uses secondary data in the form of the company's annual financial reports for five years (2016-2020). The data were analyzed using the panel data regression analysis method, and the results of the analysis found that the independent variable that had a significant and positive effect on company performance was relational capital efficiency (RCE) while the influence of other variables was found to be insignificant.